2010
DOI: 10.1055/s-0030-1250628
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Two Major Isoflavonoids in Radix Astragali on High Glucose-Induced Mesangial Cells Proliferation and AGEs-Induced Endothelial Cells Apoptosis

Abstract: Radix Astragali, the dried roots of Astragalus membranaceus var. mongholicus, is well known to have a protective effect on diabetic nephropathy. However, the effects of isoflavonoids in Radix Astragali on glomerular cells, which play a key role in the development of diabetic vascular complications, remain largely unknown. Thus, the purpose of this study was to investigate in vitro the effect of calycosin and calycosin-7-O-β-D-glucoside, two major isoflavonoids in Radix Astragali, on high glucose-induced rat me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…AGEs have been widely studied in its key role in promoting vascular dysfunction and diabetes development [Orasanu and Plutzky, 2009]. Previously, we found and reported that calycosin could ameliorate AGEs-induced apoptosis [Tang et al, 2011] and inflammation (article in revision) in EC. In the present study, we reported for the first time that a homolog of calycosin, calycosin-7-O-b-D-glucopyranoside (CG), can also protect EC from AGEs-induced apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AGEs have been widely studied in its key role in promoting vascular dysfunction and diabetes development [Orasanu and Plutzky, 2009]. Previously, we found and reported that calycosin could ameliorate AGEs-induced apoptosis [Tang et al, 2011] and inflammation (article in revision) in EC. In the present study, we reported for the first time that a homolog of calycosin, calycosin-7-O-b-D-glucopyranoside (CG), can also protect EC from AGEs-induced apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we found that calycosin-7-O-b-D-glucopyranoside (CG), a phytoestrogen, has anti-apoptotic against AGEs-induced EC apoptosis [Tang et al, 2011]. Tang and colleagues demonstrated that a homologue of CG, calycosin, could bind with estrogen receptor (ER) and promote EC proliferation [Tang et al, 2010].…”
mentioning
confidence: 99%
“…Calycosin-7-O-β-D-glucopyranoside exerted significant antiviral activities against CVB3 both in vitro and in vivo, and it is one of active ingredients in A. membranaceus for the treatment of viral myocarditis. Calycosin-7-O-β-D-glucopyranoside can also modulate endothelial cell dysfunction by ameliorating AGEs-induced cell apoptosis and inflammation [7,8].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Western blot analysis . The earliest detectable change in the course of diabetic nephropathy is an expansion of the glomerular mesangium, which is caused by mesangial cell proliferation and excessive accumulation of ECM proteins 17) . Glomerular mesangial cells, an important member of renal glomerulus, play a major role not only in physiological functions but also in pathogenesis of kidney diseases 18) .…”
Section: Effect Of Oryeong-san On Hg-induced Mapks Phosphorylationmentioning
confidence: 99%